Assignment of the structural gene encoding human aspartylglucosaminidase to the long arm of chromosome 4 (4q21----4qter). - Aula, P (1984)
The structural gene for the human lysosomal enzyme aspartylglucosaminidase (AGA) has been assigned to chromosome 4 using somatic cell hybridization techniques. The human monomeric enzyme was detected in Chinese hamster-human cell hybrids by a thermal denaturation assay that selectively inactivated the Chinese hamster isozyme, while the thermostable human enzyme retained activity. Twenty informative hybrid clones, derived from seven independent fusions, were analyzed for the presence of human AGA activity and their human chromosomal constitutions. Without exception, the presence of human AGA in these hybrids was correlated with the presence of human chromosome 4. All other human chromosomes were excluded by discordant segregation of the human enzyme and other chromosomes. Two hybrid clones, with interspecific Chinese hamster-human chromosome translocations involving the long arm of human chromosome 4, permitted the assignment of human AGA to the region 4q21----4qter.